Contemporary trends in scientific research and their influence on the categorical apparatus of jurisprudence - N. A. Bobrova (Правоприменение)
The subject of the article is trends in Russian legal science.The aim of the article is to analyze and systematize the facts accumulating in legal sciences and science studies, which develop into trends that negatively affect the state of scientific jurisprudence, its categorical apparatus and practical significance, including for lawmaking and law enforcement.Methodology. The author uses historical, sociological, formal-legal, systemic and comparative methods.The main results. The following trends have been studied: substitution of the relevance and novelty of the topic with considerations of political conjuncture, scientific fashion and other pseudo-scientific considerations; Constitutional reforms as a new round of constitutionalization in the aspect of correlation between constitutionalization and interdisciplinarity of legal sciences; the danger of escalating the interdisciplinarity of legal research into the erosion of its subject; methodological eclecticism; weighting of scientific language, negligence and incorrect use of certain legal terms; misuse of foreign terminology; disunity of science and practice of law enforcement.Conclusions. Since the degree of practical implementation of scientific and legal research into legislative and law enforcement practice is too low, a more effective mechanism for analyzing and implementing specific proposals from legal scientists is needed.